Physical Appearance in Rhythmic Gymnastics: code of point and current perceptions - Tsopani, Despina; Dallas, George; Patsantaras, Nikolaos; Irene Kamberidou; Tinto, A.; Louka, A. (ANNOUNCEMENT at the Convegno Internazionale Ginnastia Ritmica: Identita e propelmatiche di questo sport, 6-7 Aprile 2006 (Torino Italy), 2006)
Tsopani, D., Dallas, G., Patsantaras, N., Kamberidou, I., Tinto, A., & Louka, A. (2006). "Physical Appearance in Rhythmic Gymnastics: code of point and current perceptions". Announcement in Proceedings of the Convegno Internazionale Ginnastia Ritmica: Identita e propelmatiche di questo sport, (1st international Rhythmic Gymnastics Congress), 6-7 April 2006, Torino Italy.  DOI: 10.13140/RG.2.1.1482.4161  <a href="https://www.researchgate.net/profile/Irene_Kamberidou/publication/274955910_Physical_Appearance_in_Rhythmic_Gymnastics_code_of_point_and_current_perceptions/links/55d5bb7708aed6a199a0d492.pdf?ev=pub_int_doc_dl&origin=publication_list&inViewer=true">Physical Appearance in Rhythmic Gymnastics, April 2006, Torino Italy.pdf     [K.6 in Apella]